Linkages between the southern Patagonia Pre-Permian basements: new insights from detrital zircons U-Pb SHRIMP ages from the Cerro Negro District - Permuy Vidal, Conrado (2014)
The Patagonian basement rocks are dominated by Precambrian to Early Paleozoic metamorphic rocks intruded by Paleozoic granitoids. Recently discovered basement rocks in the Cerro Negro District are characterized mainly by quartz-muscovite-chlorite schists; the metamorphic grade reaches greenschist facies (biotite-garnet grade) with a regional S1 schistosity subparallel to the original sedimentary structure S0 and a secondary non-penetrative S2 foliation. New detrital zircon U-Pb geochronology shows that maximum depositional ages for detrital zircons are Devonian, ages of 379 ± 4Ma. These results suggest that the Cerro Negro basement rocks are the youngest basement in the Deseado Massif, overlapping some detrital zircon ages in the eastern Andean Metamorphic Complex in the Andean region. Most of detrital zircons are igneous in origin with a major peak around ~396Ma, probably sourced from the Devonian granitoids of the Río Deseado Complex (El Laurel and Bahía Laura granites) and equivalent northern Patagonia granitoids (e.g. Colan Conhué and Lago Lolog granites). Secondary peaks correspond to Ordovician to Silurian ages, being the Río Deseado Complex and La Modesta Formation (and their igneous contributors) the possible sources of the zircons. The minor oldest peaks yield Cambrian-Neoproterozoic; Mesoproterozoic and Paleoproterozoic-Archean ages, evidencing a common source from the interior of Gondwana. The results provide new insights about the relationships between the pre-Permian metasedimentary rocks of the extra-Andean and Andean region during Mid-Paleozoic age